Host status of soybean genotypes to Meloidogyne arenaria and Meloidogyne morocciensis - Dalla Nora, Daiane; Balardin, Ricardo Rubin; Kaspary, Tiago Edu; Souza Júnior, Ismail Teodoro de; Bellé, Cristiano (Revista de Ciências Agroveterinárias, 2020)
Soybean crop productivity is limited by several biotic factors, particularly plant-parasitic nematodes. Several species have been reported to cause crop damage, especially those of the genus Meloidogyne. Therefore, the aim of this study was to evaluate, the reaction of 28 soybean genotypes to Meloidogyne arenaria and M. morocciensis in a greenhouse. The soybean genotypes were the same for experiments with different species of plant-parasitic nematodes and were individually inoculated with 5,000 eggs + second-stage juveniles (J2) of Meloidogyne and kept in a greenhouse. After 60 days of inoculation, the roots of each plant were assessed for the number of galls, final population, and reproduction factor (RF = final population/initial population). The averages of the different variables were then compared to each other by the Scott-Knott cluster analysis at a significance level of 5%. All of the soybean genotypes in the study were susceptible to both nematodes, with RF ranging from 3.5 to 24.1 for M. arenaria and 5.3 to 37.5 for M. morocciensis.